2013
DOI: 10.7763/ijimt.2013.v4.406
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Effectiveness of the “Dogs of the Dow” Strategy for the Thai Stock Investment

Abstract: In stock markets, investors always seek ways to make profit or outperform benchmarks. However, this aim is not easy to achieve even for professional fund managers. In this study, we propose applying the "Dogs of the Dow" investment strategy to the Thai market. With this strategy, we buy the ten highest yielding SET50 (Stock Exchange of Thailand 50) stocks and rebalance the portfolio annually. We conduct a simulation for data from 1995 to 2012. The simulation result shows that on average, the "Dogs of the Dow" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…Using data in Pakistan, Soomro Haroon (2015) also showed that the DoD theory works well with some limitations applied. Earlier similar results were found in a study by Tissayakorn et al (2013), who showed the outperformance by the DoD theory in the Thai stock market. Chong and Luk (2010) also confirmed the theory using blue-chip stocks of the Hang Seng Index in Hong Kong.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Using data in Pakistan, Soomro Haroon (2015) also showed that the DoD theory works well with some limitations applied. Earlier similar results were found in a study by Tissayakorn et al (2013), who showed the outperformance by the DoD theory in the Thai stock market. Chong and Luk (2010) also confirmed the theory using blue-chip stocks of the Hang Seng Index in Hong Kong.…”
Section: Introductionsupporting
confidence: 85%
“…However, there is no robust consensus on the validity of the theory in the market. Some have found the theory to be well confirmed (Chong & Luk, 2010;Tissayakorn et al, 2013;Soomro & Haroon, 2015;Yan et al, 2015), whereas other studies contradict the theory (Domian et al, 1998;Hirschey, 2000;Da Silva, 2001;Kim, 2019). Yan et al (2015) supported the validity of DoD theory by demonstrating higher returns upon following this strategy than the average market return in Taiwan.…”
Section: Introductionmentioning
confidence: 91%
“…Many researchers have worked on the validity of the DoD theory, but with a lack of a strong consensus. Using data in Taiwan and Thai stock markets, respectively, Yan et al (2015) and Tissayakorn et al (2013) showed that the DoD strategy earned higher returns than the benchmark in each country. Soomro and Haroon (2015) also confirmed that the DoD strategy outperformed the benchmark in the Pakistani market, with some limitations.…”
Section: Introductionmentioning
confidence: 99%